(untitled) (Global Journal of Human-Social Science, 2020)
Focus is a very important element in the world of education to increase the effectiveness of other learning skills such as reading, writing and calculating. The lack of focus issue existed as the pupils were uninterested and unmotivated to learn. This has caused disruptive behaviours in the classroom which affected both teachers and pupils. An intervention was essential in curbing this problem. Hence, this study was embarked to identify the effectiveness of the Mandala Colouring Therapy in increasing Year 3 pupils’ focus during the initial lesson of the day. A mixed method study was conducted at 5 national schools in Temerloh, Pahang. The participants were 100 Year 3 low average pupils and 20 teachers who taught initial lesson periods. The data was collected through interviews and questionnaires These quantitative data was analysed using frequency counts on SPSS, while the qualitative data was analysed using Burnard’s method. The overall findings revealed that pupils’ interest and focus has been increased with Mandala Colouring Therapy.